The Form of Daily Use in Language (Javanese Language Dialect) on Early Children Age 5-6 Years - Krisnaningrum, Dwi; Sularti Dewanti Handayani, Sri (Jurusan PGPAUD FIP UNNES, 2020)
Daily forms of language use, especially the Javanese dialect in early childhood, have diversity between one child and another. It is influenced by differences in the backgrounds in which they live. As in the use of the sentences,